Decentralisation: A multidisciplinary perspective - Balázs Bodó; Jaya Klara Brekke; Jaap-Henk Hoepman (Internet Policy Review, 2021)
Decentralisation as a concept is attracting a lot of interest, not least with the rise of decentralised and distributed techno-social systems like Bitcoin, and distributed ledgers more generally. In this paper, we first define decentralisation as it is implemented for technical architectures and then discuss the technical, social, political and economic ideas that drive the development of decentralised, and in particular, distributed systems. We argue that technical efforts towards decentralisation tend to go hand-in-hand with ambitions for rearranging power dynamics. We caution, however, against simplistic understandings of power in relation to the decentralisation-centralisation spectrum, and argue that in practice, decentralisation might very well be served by and produce centralising effects. The paper then goes on to discuss the critical literature that highlights some of the common assumptions and critiques made about decentralisation and the pros and cons of a decentralised approach. Finally, we propose some of the missing parts to current debates about decentralisation, and argue for a more nuanced and grounded approach to the centralisation/decentralisation dichotomy.
Keywords: 300; Decentralisation